Epithelial-Mesenchymal Transition and Its Regulation Mechanisms in Pancreatic Cancer - Luu, Tuan (Frontiers in Oncology, 2021)
As one of the malignancies with high mortality and high insensitivity to existing therapies, pancreatic cancer and mechanisms underlying its progression have received growing scholarly attention. The role of the epithelial-mesenchymal transition (EMT) in pancreatic cancer genesis and metastasis has been reported albeit controversy has remained. Recent insights into further EMT-regulating mechanisms underlying pancreatic cancer contribute to the nexus between EMT and this cancer type. This review will elucidate the role of EMT as a hallmark for pancreatic cancer as well as summarize EMT-regulating factors recently detected as a key advance in the research stream on EMT in pancreatic cancer.